Envelhecimento: modulação da produção de óxido nítrico, fagocitose e citocinas anti e pró-inflamatórias pela noradrenalina e ácido caféico em granelócitos humanos - Raquel Cunha Lara (2013)
It is known today that many stimuli from the CNS are capable of modulating immune responses. The endocrine system and, in particular, one of the HPA axis is responsible for many links between these two systems. The caffeic acid is a phenolic acid found in many agricultural products, which have antioxidant actions. Thus, the aim of our study was to evaluate the modulating effect of Noradrenaline and caffeic acid, on the production of nitric oxide, the process of phagocytosis and cytokine anti and pro-inflammatory granulocytes in humans, during the aging process. Granulocytes (1x106) from healthy donors between 20-60 years, of both sexes, divided into three groups: 1 - 20-39 years 2 - 40 to 60 years, 3- 60 to 80 years, in four different ways, namely: [A] Granulocytes 1x106 [B] Granulocytes 1x106 Noradrenaline 10-9M + [C] Granulocytes 1x106 caffeic acid 500 uM + [D] + Granulocytes 1x106 Noradrenaline 10-9 M + caffeic acid 500 uM. These acid concentrations were determined from concentration-response curve. To evaluate the modulating effect of caffeic acid and norepinephrine, phagocytosis and nitric oxide production tests were used. To assess modulation of anti-inflammatory action IL-4,IL-10 and IL-8 dosage by ELISA "sandwich" was carried. Statistical analysis was performed using the nonparametric Mann-Whitney test and ANOVA followed by Tukey post-test; with p <0.05 considered statistically significant. Our results showed that there is a reduction (p <0.05) in phagocytic capacity of 32% (20 - 39 years) to 20% (40-60 years), and 6% (60-80 years) when caffeic acid (CA) is incubated with noradrenaline (NA). NO production assay verified that the AC is able to increase (p <0.05) NO production of NA in 49% in the age group of 20-39 years. In the group aged between 40-60 years and 60-80 years, it was found a reduction (34%) and (8%), respectively; in the ability of the AC in its modulating effect on NA. In evaluating whether this drop in the modulating effect of AC on the NA could be related to anti-inflammatory cellular mechanisms our next step was to quantify IL-4,IL-10 and IL-8. In the age group of 20-39 years the AC was able to reduce (p <0.05) IL-4 production generated by NA in 22%. However, when evaluating the effect of AC aged 40-60 years it was found a reduction of this effect (17%), and 60-80 years found reduction of 3%. As IL-10 perceive 16% activation of 20-39 year, 18% inhibition (40-59 years) and 16% inhibition (60-80 years). Finally, IL-8 have 91% decrease of 20-39 years, followed by inhibition of 54% and 16% respectively, between 40-59 years and 60-80 years. Our results showed that caffeic acid can modulate the effect of noradrenaline in the parameters analyzed, namely phagocytosis, production of NO, IL-4, IL-10 and IL-8. We also found that the aging process alters the action of caffeic acid on the mechanisms antioxidant and anti-inflammatory and these may be related to decreased effect of norepinephrine on the HPA axis.